2013
DOI: 10.1177/0956462413481528
|View full text |Cite
|
Sign up to set email alerts
|

Raltegravir-induced Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) syndrome – Implications for clinical practice and patient safety

Abstract: This case report describes two severe antiretroviral drug adverse reactions that occurred in the same patient. A 55-year-old HIV-positive African woman received a single epidural triamcinolone injection for pain relief of postherpetic neuralgia. Forty-one days later, she developed severe iatrogenic Cushing's syndrome due to the drug-drug interaction between triamcinolone and her boosted protease inhibitor therapy. The patient's antiretroviral regimen was thus changed to replace her protease inhibitor with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 7 publications
0
22
0
2
Order By: Relevance
“…Although raltegravir-induced DRESS syndrome is highly uncommon, our is the third documented case,14 15 which highlights the possibility that raltegravir may be associated with DRESS syndrome more often than previously believed.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Although raltegravir-induced DRESS syndrome is highly uncommon, our is the third documented case,14 15 which highlights the possibility that raltegravir may be associated with DRESS syndrome more often than previously believed.…”
Section: Discussionmentioning
confidence: 65%
“…Based on the exclusion of other potential causes, as well as these new biochemical findings, a diagnosis of DRESS syndrome was made and raltegravir was identified as the most likely cause given the temporal relationship of her clinical symptoms and timing of the initiation of raltegravir. Additionally, a literature review revealed two prior cases of DRESS associated with raltegravir 14 15. Of note, the pulmonary nodules were suspected to be secondary to DRESS syndrome versus an infectious process as all cultures were unrevealing.…”
Section: Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, virtually all HIV antiretroviral agents can cause rash, but very few are associated with eosinophilia, such as drug reaction with eosinophilia and systemic symptoms (DRESS), which has been well-described with nevirapine and raltegravir [1113]. …”
Section: Pathophysiology and Etiology Of Eosinophiliamentioning
confidence: 99%
“…However, many of the rash events have been confounded by use of concomitant medications associated such as NNRTIs, ABC and protease inhibitors. More recently there have been cases of raltegravir associated DRESS/DIHS and SJS/TEN with three separate case publications of raltegravir associated DRESS/DIHS syndrome all in women of African descent 60-62 . A newly approved integrase inhibitor, dolutegravir has not been associated with rash.…”
Section: Integrase Inhibitorsmentioning
confidence: 99%